Bibliometric Analysis of Digital Loyalty Programs - Loso Judijanto; Muhamad Ammar Muhtadi; Sintia Permata Sari (Westscience Press, 2026)
Digital loyalty programs have emerged as an essential aspect of customer relationship management that helps firms build retention capabilities and sustain competitive advantage in volatile digital markets. In this study, an attempt is made to conduct a bibliometric analysis to investigate the intellectual structure, research trends, key contributors, and emerging themes in digital loyalty program scholarship. The data were collected from the Scopus database using keywords